The Effect of Drought on Forest and Grassland Fire in South-east of Caspian Sea: a Case Study in Golestan Province (1998-2008) - Bay, Naser; Semnani, Alireza Abbasi; Mazini, Fereshte; Ataei, Hushmand; Fakhri, Siros; Khalili, Maede; Gadnomkar, Amir; Montazeri, Majid (International Journal of Bio-resource and Stress Management, 2023)
Golestan province, Iran is a prey to fire every year, current study takes into account the data of rain and examines the drought effect and its intensity on Golestan forest fires. The results of rainfall disorders index showed that 3 widespread drought period, 3 regional droughts happened in recent 11 years in this region, and in other years it had reasonable rainfall and drought was less than regional drought. But in monthly periods, different intensity of drought happened in this province. Finally, it becomes clear that yearly drought can not be used for analyzing the forest fires in Golestan province, but intensity of monthly drought in the regression equation confirms the direct effect of droughts over fires. 14% of fires in Golestan province occurred in wet months which include 10% of affected area from drought. Mean while much intensified droughts which take 10% of fires, cause 24% of burned area (1468 acre).